Digital financial inclusion and comprehensive multilevel medical insurance system in China - Liu, Zhe; Wu, Xingyuan; Chen, Xi; Qin, Congzhi; Qiu, Zenghui; Fang, Zhuangzhi; Yao, Lan (Frontiers in Public Health, 2025)
BackgroundThe influence of digital financial inclusion on medical insurance systems has drawn significant attention. However, its impact on China’s multilevel medical insurance system (MMIS) remains uncertain. The MMIS is crucial for societal wellbeing. It safeguards citizens from financial hardships during medical treatment, especially as the population ages and healthcare costs rise. By covering medical expenses, the MMIS ensures equal access to essential medical services, protecting people’s health rights and preventing impoverishment caused by medical expenses, thus promoting social stability and equity. This study used panel data from 31 provinces in China from 2016 to 2020 to explore the impact of digital financial inclusion on the development of the MMIS.MethodsAn MMIS development matrix was constructed using the entropy weight method and the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS). Panel data regression models were employed to analyze the effects of different dimensions of digital financial inclusion on the MMIS.ResultsThe overall digital financial inclusion index, particularly the “coverage” dimension, had a significant positive and significant impact on the MMIS (p < 0.05). However, the “depth” and “digitization” dimensions were statistically insignificant (p > 0.1). Robustness checks using lagged instrumental variable approaches and double machine learning (DML) methods confirmed the stability of these findings. Heterogeneity analysis using the causal forest model revealed that digital financial inclusion had a more pronounced effect in central and western regions. Its impact in the eastern regions was relatively weaker, highlighting significant regional disparities.ConclusionDigital infrastructure in the central and western regions must be strengthened to enhance financial inclusion coverage and service capacity; the depth and quality of financial services in the eastern regions should be improved to optimize the effects of digital finance on the MMIS. Deeper integration between digital financial inclusion and the MMIS should be prompted through technological innovations to improve both equity and sustainability. This study provides valuable insights for policymakers to address regional disparities in further developing the MMIS.